PENGGUNAAN METODE PROBLEM SOLVING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA PELAJARAN MATEMATIKA TENTANG LINGKARAN DI KELAS VIII A SMPN 11 MADIUN TAHUN PELAJARAN 2015/2016 - Dwi Ratnasari Dewi (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
Research carried out by two cycles, in which the first cycle of students working on quiz questions given by the teacher. Students noted the difficulties experienced while working on quiz questions received. Teachers and students discuss the material they are having trouble students. While in the second cycle, there is an additional action, the students were asked to present the quiz questions that come in front of the class. Students expressed difficulty verbally, another friend who helped work on the class. The results of the study before the first cycle, the first cycle and the second cycle increased. From the test results obtained by the average value of the first cycle = 68,75. Cycle II, = 87,75. Level classical completeness of each cycle rises of 48% and in the second cycle be 90,625%. Observation of learning activities more alive with many questions asked by the students.The conclusion of this study is the use of problem solving methods can increase student achievement in math on the circle A class VIII SMPN 11 Madiun in academic year 2015/2016.